ANALISIS MISKONSEPSI BIOLOGI BERBASIS TES DIAGNOSTIK FOUR-TIER MULTIPLE CHOICE BERBANTUAN CRI PADA MATERI PERUBAHAN LINGKUNGAN DI SMA NEGERI 3 SAMARINDA - Purwaningsih, Purwaningsih; Masitah, Masitah; Nasution, Ruqoyyah; Jailani, Jailani (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
This study analyzes biology misconceptions using a Four-Tier Multiple Choice diagnostic test supported by the Certainty of Response Index (CRI) on the topic of environmental change and preservation among Grade X students at SMA Negeri 3 Samarinda. The research employed a descriptive design involving 280 students from eight Grade X classes. The instrument used was a 10-item Four-Tier Multiple Choice test integrated with the CRI to assess both conceptual understanding and students’ confidence in their answers. Data were analyzed using Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing. The results showed that the average misconception rate among students was 50.64%, categorized as moderate. The highest rate of misconception (66.43%) was found in the indicator related to the causes of environmental change, classified as high. The findings indicate that the use of a Four-Tier Multiple Choice diagnostic test with CRI is an effective tool for identifying misconceptions in biology. Therefore, targeted instructional interventions are necessary to address these misconceptions and improve students' conceptual understanding.